2017
DOI: 10.3389/fphar.2017.00597
|View full text |Cite
|
Sign up to set email alerts
|

Population-Based Case-Control Study Assessing the Association between Statins Use and Pulmonary Tuberculosis in Taiwan

Abstract: Background and Objectives: Little evidence is available about the relationship between statins use and pulmonary tuberculosis in Taiwan. The aim of the study was to explore this issue.Methods: Using the database of the Taiwan National Health Insurance Program, we conducted a population-based case-control study to identify 8,236 subjects aged 20 years and older with newly diagnosed pulmonary tuberculosis from 2000 to 2013 as the cases. We randomly selected 8,236 sex-matched and age-matched subjects without pulm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…Of these, 12 were further excluded because two of them did not treat statin use as the exposure, six did not report tuberculosis infection as the outcome, one study did not provide available outcome data, and the other three were abstracts of already included studies. Finally, nine observational studies were included (10)(11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Literature Searchmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these, 12 were further excluded because two of them did not treat statin use as the exposure, six did not report tuberculosis infection as the outcome, one study did not provide available outcome data, and the other three were abstracts of already included studies. Finally, nine observational studies were included (10)(11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Literature Searchmentioning
confidence: 99%
“…These studies were published between 2014 and 2019, and all of them included Asian people. Regarding the study design, five studies were retrospective cohort studies (10,(15)(16)(17)(18), one was a prospective cohort study (11), two were nested case-control studies (12,14), and another one was a retrospective case-control study (13).…”
Section: Study Characteristics and Quality Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…A reduction in membrane cholesterol decreases the entry of TB pathogen inside macrophages [8]. Retrospective human studies and experimental animal studies have shown beneficial effects of statins in both treatment and prevention of TB [10][11][12]. Classic first-line TB treatment consists of four drugs: rifampicin, isoniazid, pyrazinamide, and ethambutol.…”
Section: Introductionmentioning
confidence: 99%